Sebab-Sebab Misinterpretasi dalam Al-Qur'an - Mar'atus Sholihah (FALASIFA : Jurnal Studi Keislaman, 2016)
The Causes of Misinterpretation in the Qurâ€™an. Islam becomes the largest religion in the world today which makes most of everybody knows what is Islam and what is Qurâ€™an. A deep understanding about truly Islam and Qurâ€™an is needed, because everybody in this particular time can interpret Moslemâ€™s holy book, Qurâ€™an. A lack of understanding the Qurâ€™an and reading or learning it from unqualified sources can take Moslems losing their true knowledge and faith. Liberty of speech and argumentation appears with some interpreters to write and speak about the content of Qurâ€™an and disseminate it to society, including orientalists who have been becoming very famous in Islamic world with their explanations about Qurâ€™an and Hadits. Some orientalists certainly have a good understanding about it which make their works are able being references for Moslems and everyone who is interested in studying Qurâ€™an. Others, interpret the Qurâ€™an and Hadits to destroy the true content of it. Interpreters who do not have a pure purpose interpreting Qurâ€™an are not only from orientalists, but also from its own religion, Moslems. Their orientation interpreting Qurâ€™an is not for peopleâ€™s reconciliation, but it is more for their own importance and political interest of themselves, especially who follow their passions. Several Moslem interpreters have no high quality in Arabic to interpret it and do not follow interpretation rules which have been compromised. Those aspects can absolutely cause misinterpretation in the Qurâ€™an. Â Keywords: Islam, Moslems, Qurâ€™an, interpretation, interpreters